Analisis Penentuan Prioritas Jenis Penyakit Pada Praktik Terapi Babe Dengan Metode Weighted Product - Inayah Sabila (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
The increasing number of patients with various diseases at the Babe Therapy Practice requires an effective method to determine which diseases should be prioritized in handling. This study aims to analyze the prioritization of disease types using the Weighted Product (WP) method as a decision support approach. Data were obtained through interviews with the practitioner (Babe) and observations of patient records covering seven disease types: uric acid, rheumatism, hypertension, pinched nerves, stomach acid, vertigo, and GERD. The criteria considered include visit frequency, severity level, therapy duration and therapy cost. Each criterion was given a specific weight based on its level of importance. The calculation results using the WP method show that uric acid (gout) ranks highest, indicating it should receive priority treatment due to its potential to cause kidney complications. This study contributes to the application of decision support systems in therapy practices to improve service effectiveness and patient management.